(untitled) (Materiali di Estetica. Terza serie, 2019)
We explore one of Dorfles’ many cultural contributions: his collaboration with the magazine Civiltà delle Macchine. That review, whose founder and editor was the major Italian poet Leonardo Sinisgalli, investigated the fields across “literary” and “scientific” knowledge. Dorfles dealt with specific issues about industrial design (furniture, design schools, historical developments), but also outlined a theory of industrial aesthetics, fully connected with his wider art history approach.